1988
DOI: 10.2134/agronj1988.00021962008000030022x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tillage Practices on Phosphorus Distribution and Forms in Three Ultisols

Abstract: Many studies have indicated that organic matter levels in soils tend to rise when no-till (NT) management replaces plowing. It was hypothesized that organic P may thus play a more important role in the plant availability of P in NT soils. A laboratory study was conducted to investigate the organic and inorganic forms of P and their cycling in NT and conventionally tilled (CT) silt Joams. Soils from three long-term field experiments were sampled in the fall of 1984, obtaining core segments from 0 to 2, 2 to 4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
22
1
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 14 publications
6
22
1
2
Order By: Relevance
“…In Sc3 and Sc4, nutrients accumulated in the surface layer due to retention of higher amounts of residue rich in plant nutrients and minimal soil disturbance, whereas under conventional practices residues were removed and remaining stubbles thoroughly incorporated in the plough layer (0–20 cm) by tillage operations. CA-based practices, particularly conservation tillage are reported to cause greater accumulation of nutrients in surface layer compared to conventional tillage (Holanda et al 1998; Lopez-Fando and Pardo 2009). The concentration of available N in soil under all the scenarios was quite lower than the lower limit of 260 kg N ha −1 which can be attributed to immobilization of inorganic N in soil (Locke and Hons 1988).…”
Section: Resultsmentioning
confidence: 99%
“…In Sc3 and Sc4, nutrients accumulated in the surface layer due to retention of higher amounts of residue rich in plant nutrients and minimal soil disturbance, whereas under conventional practices residues were removed and remaining stubbles thoroughly incorporated in the plough layer (0–20 cm) by tillage operations. CA-based practices, particularly conservation tillage are reported to cause greater accumulation of nutrients in surface layer compared to conventional tillage (Holanda et al 1998; Lopez-Fando and Pardo 2009). The concentration of available N in soil under all the scenarios was quite lower than the lower limit of 260 kg N ha −1 which can be attributed to immobilization of inorganic N in soil (Locke and Hons 1988).…”
Section: Resultsmentioning
confidence: 99%
“…is reduced substantially under a ZT system, which may lead tiilage may lead to breakdown of organic matter, lois of soil to organic matter and the relatively immobile plant nutrients, mois-ture, spread of salinity, and inJreased susceptibility to such-as P and K, being concentrated in the upper soil layers wind and wlter erosion (Carnpbell et al 1990; drant ei al. (Weil et al 1988;Robbins and voss 1991). Availability and 1992).…”
mentioning
confidence: 99%
“…Moving to a reduced or zero-till (ZT) cropping system distribution of the more mobile nutrients, such as NO3-N can combat soil degradation but may'affect itre itryrlcut, and SOa-S, may also.be affected under ZT, as a result of chemical and biolog-ical properties oi the soil iOoran and the changes in soil mixing,.soil water content, soil porosity Smith 1987). Undei a lT iyrt"-, the surface profile of and orginic matter breakdown (Doran and Smith-1987)' the soil tended to become somewhat -or" .o-puit (Grant Distribution of nutrients in the soil prohle can affect the and Lafond 1993), while moisture conservation increased availability of nutrients to the growing plant, as well as (Lafond et al 1992 (Weil et al 1988;Dalal 1989;,r, "nnun (Campbelllt al. 1990).…”
mentioning
confidence: 99%
“…Previous research under long-term no-tillage (NT) management has shown higher amounts of available P in the surface thin layer (0 to 5 cm or less) under NT than CT (Eckert 1985;Weil et al, 1988;Karlen, 1991;Ismail et al, 1994;Selles et al, 1997;Selles et al, 1999;Lupwayi et al, 2006, Mathers & Nash, 2009, Cade-Menun et al, 2010. Similarly, in our study, the amounts of extractable P in the surface 0-7.5 cm soil layer were greater under NT compared to RT, but the amounts of extractable P in the 7.5-15 and 15-20 cm layers were greater with RT compared to NT.…”
Section: Discussionmentioning
confidence: 99%